FINANCIAL RATIOS OF PT PURADELTA LESTARI Tbl. UNDER THE INFLUENCE OF THE GLOBAL ECONOMIC CRISIS IN 2022 - Rahma, Zhafira Yaziar; Yustika, Gaung Perwira (Jurnal Manajemen Bisnis dan Terapan, 2000)
PT Puradelta Lestari (DMAS) is one of the companies engaged in the property sector and is part of the Sinar Mas Land group. The purpose of this research paper is to analyze the financial ratios of PT DMAS whether the company's shares are still worth buying and holding in the next few years and how PT DMAS's attitude in facing the global economic crisis in early 2023 which makes some of the company's businesses sluggish, one of which is in the property sector. This analysis uses current ratio, quick ratio, cash ratio, GPM, OPM, NPM, ROI, ROA, DAR, DER, EPS, PER, and MBV, most of which calculations use data on net income, total equity, current liabilities, total assets, stock prices and other data in the company's financial statements. The analysis results show that PT DMAS has a current ratio of 4.82, quick ratio of 2.27, cash ratio of 0.97, GPM of 71.16%, OPM of 60.89%, NPM of 63.06%, ROA of 18.70%, ROI of 276.02%, DAR of 13.57%, DER of 15.70%, EPS 25.26, PER 6.29x and MBV 1.34x. These results indicate that PT DMAS shares are still worth holding in the next few years, even though at the beginning of the first trimester report in 2023 PT DMAS experienced a decrease in revenue from the previous year due to various factors, both post-Covid-19 pandemic recovery and the global economic crisis that is sweeping the world.